Efeito de estratégia de suplementação com concentrado no desempenho de cabras mestiças Saanen, em dois sistemas de produção - Macedo, Vicente de Paulo [UNESP]; Damasceno, Júlio Cesar [UNESP]; Santos, Geraldo Tadeu dos [UNESP]; Martins, Elias Nunes [UNESP]; Macedo, Francisco de Assis F. [UNESP]; Canto, Marcos Weber do [UNESP] (FapUNIFESP (SciELO), 2002)
The experiment was carried out to evaluate the performances of cross breed Saanen dairy goats submitted to two strategies of supplementation with concentrate 30% of daily requirements in net energy (NRC, 1981) supplied by concentrate, from third week until the end of lactation (ESC. 1) or 60% of requirements from the 3rd to the 13th week of lactation and 15% from 14th until the end of lactation (ESC.2); and evaluate the animal response to these strategies of supplementation with concentrate in a semi-confined or pasture systems. Thirty one animals were used in a completely randomized design. The system of production affected the total intake of concentrate and total milk production; at pasture system the values for these two variables were higher. The supplementation with concentrate affected the total intake of concentrate and total production of milk and the relation of milk/consumption of concentrate. The highest value for relation of milk/consumption of concentrate and the least for the total consumption of concentrate were obtained at ESC. 1. Body weight affected of the system of production, resulting in a higher value to the system of pasture. Weight and body condition had different responses to he supplementation with concentrate according to the system of production. The semi-confined system ESC.2 resulted in a higher value to the body condition; the body weight was no affected. At pasture system the highest values for weight and body condition were obtained in the supplementation with concentrate ESC. 1. Reproductive parameters did not affect supplementation with concentrate and system of production.
Effect of supplementation level with concentrate on performance of the crossbred Saanen dairy goats, in two production systems
Keywords: Body condition and weight; Milk production; animal experiment; body constitution; body weight; controlled study; cross breeding; dairying; diet supplementation; energy resource; food intake; goat; lactation; milk production; nutritional requirement; pasture; randomization; Capra hircus